Establishment of a CRISPR-Based Lentiviral Activation Library for Transcription Factor Screening in Porcine Cells - Yingjuan Liang; Xiaoxia Yao; Jingxin Han; Jinpeng Wang; Xiao Zhang; Donglin Zhao; Chaoqian Jiang; Lishuang Geng; Shihao Lv; Zhonghua Liu; Yanshuang Mu (Animals)
Transcription factors play important roles in the growth and development of various tissues in pigs, such as muscle, fat, and bone. A transcription-factor-scale activation library based on the clustered, regularly interspaced, short palindromic repeat (CRISPR)/CRISPR-associated endonuclease Cas9 (Cas9) system could facilitate the discovery and functional characterization of the transcription genes involved in a specific gene network. Here, we have designed and constructed a CRISPR activation (CRISPRa) sgRNA library, containing 5056 sgRNAs targeting the promoter region of 1264 transcription factors in pigs. The sgRNA library, including sgRNA with MS2 loops, is a single-vector system and is packaged with lentivirus for cell screening. Porcine PK15 cells expressing the porcine OCT4 promoter driving EGFP, dCas9 fused with VP64, and MS2-binding protein-p65-HSF1 were constructed, and then, the sgRNA activation library was used to screen the transcription factors regulating OCT4 expression. After the lentiviral transduction and deep sequencing of the CRISPR sgRNAs library, the highest ranking candidate genes were identified, including 31 transcription factors activating OCT4 gene expression and 5 transcription factors inhibiting OCT4 gene expression. The function and gene regulation of the candidate genes were further confirmed by the CRISPR activation system in PK15 cells. The CRISPR activation library targeting pig transcription factors provides a promising platform for the systematic discovery and study of genes that determine cell fate.